The Patron and the Garden: Sir David Lindsay and Edzell Castle, 1604. Issue 1 (November 2015) - Brown, Marilyn
Abstract : Charles McKean understood architecture as the reflection of the patron's social status and sense of place. Edzell Castle is the foremost example in Scotland of the patron choosing to display the important concerns of his intellectual and political life through his garden. In 1604 James VI tried to secure a union of England and Scotland and, emblematically, through his garden Sir David Lindsay celebrated the hoped-for Magna Britannia. Research into the sculptured panels of the Seven Planetary Deities, the Seven Liberal Arts and the Seven Virtues traces their origins in northern Europe c .1600 and bears further witness to the breadth and extent of his interests and contacts.